The speech act of agreement and ways of expressing it - Nusratullayeva, Shoxista (The Lingua Spectrum, 2025)
This article investigates the speech act of agreement from pragmalinguistic perspective noticing its importance in everyday human interaction. Based on fundamental theories by Austin (1962) and further developed by Searle (1969, 1979), agreement is primarily examined as an illocutionary act – a communicative activity that expresses the speaker's intent. Utilizing the politeness theories of Brown and Levinson (1987) and Leech’s (1983) Agreement Maxim, the article recognizes agreement as an essential technique for preserving social harmony and fostering strong interpersonal interactions. This study examines the cultural differences in expressions of agreement, focusing on differences in directness, vocabulary choice, and politeness technique based on insights from cross-cultural studies, especially the Cross-Cultural Speech Act Realization Project by Blum-Kulka et al. (1989). The article classifies agreements into upgraded, repetitive, and downgraded strategies using Conversation Analysis, particularly the seminal work of Pomerantz (1984). Real-world conversational examples are used to highlight the pragmatic subtleties of each strategy.